2014
DOI: 10.1371/journal.pone.0087678
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization of the Crustose Coralline Alga Porolithon onkodes to Variable pCO2

Abstract: Ocean acidification (OA) has important implications for the persistence of coral reef ecosystems, due to potentially negative effects on biomineralization. Many coral reefs are dynamic with respect to carbonate chemistry, and experience fluctuations in pCO2 that exceed OA projections for the near future. To understand the influence of dynamic pCO2 on an important reef calcifier, we tested the response of the crustose coralline alga Porolithon onkodes to oscillating pCO2. Individuals were exposed to ambient (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 89 publications
8
66
0
2
Order By: Relevance
“…Nonetheless, there are consis tent trends across two major functional groups (i.e., calcareous species vs. "fleshy" algae and marine plants) to CO 2 enrich ment among macrophyte species from the NECAN study area. The vulnerability of calcareous algae and the increased pro ductivity among fleshy algae and marine plants in response to elevated pCO 2 are consistent with several metaanalyses from other ecosystems (Kroeker et al, 2010(Kroeker et al, , 2013Johnson et al, 2014).…”
Section: Oca Effects On Macrophytessupporting
confidence: 85%
“…Nonetheless, there are consis tent trends across two major functional groups (i.e., calcareous species vs. "fleshy" algae and marine plants) to CO 2 enrich ment among macrophyte species from the NECAN study area. The vulnerability of calcareous algae and the increased pro ductivity among fleshy algae and marine plants in response to elevated pCO 2 are consistent with several metaanalyses from other ecosystems (Kroeker et al, 2010(Kroeker et al, , 2013Johnson et al, 2014).…”
Section: Oca Effects On Macrophytessupporting
confidence: 85%
“…Different responses of P. onkodes to high pCO 2 in different locations in this study (as well as among previous studies [12,52]) suggest that in contrast to H. macroloba, massive Porites and P. damicornis, the response of P. onkodes to OA may be influenced by the environmental history prior to collection. At local scale, coralline algae experiencing naturally diel pH variations are acclimatized to variable pH [29], and some temperate species found in habitats exposed to large pH changes (i.e. tidal pools) are more resistant to OA than species living in habitats characterized by more stable pH [28].…”
Section: Discussionmentioning
confidence: 99%
“…These problems can be reduced by conducting identical OA experiments at multiple locations, but such work remains technically challenging, not least because the environmental conditions to which organisms have been exposed (i.e. saturation states, temperature) on the reef prior to the experiment also are likely to vary among locations, and potentially can confound the contrast of interest [28,29]. In this study, we compared the response of reef calcifiers to OA at multiple locations on a regional scale and used among-location differences in physical conditions to our advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, skeletal mineralogy was likely the more important factor controlling the calcification response of the 3 species investigated. On the other hand, Johnson et al (2014) reported that P. onkodes collected from a habitat with high pCO 2 variability were more resistant to high pCO 2 than individuals collected from a habitat with stable pCO 2 , although both populations decreased calcification rates when exposed to 660 μatm pCO 2 . Because P. onkodes is a dolomite-depositing alga, populations growing in the pCO 2 -variable environment may have accumulated dolomite in their skeletons (which has been shown to occur in this species; Diaz-Pulido et al 2014), making them more resistant to experimental pCO 2 conditions.…”
Section: Synergistic Effectsmentioning
confidence: 95%